Penerapan Prinsip First to file Dalam Sengketa Merek Terkenal - Tanjung, Damar Ramadhanna; Njatrijani, Rinitami; Rahmanda, Bagus (Faculty of Law, Diponegoro University, 2023)
The “Superman” brand dispute between DC Comics and PT Marxing Fam Makmur was caused by the use of the first to file principle where the “Superman” brand owned by DC Comics could not be registered because the mark had already been registered by PT Marxing Fam Makmur. This study uses a normative juridical approach. The purpose of this study is to determine the legal protection for bad faith towards the well-known brand, namely